Numerical treatment for a novel crossover mathematical model of the COVID-19 epidemic - Fawaz K. Alalhareth; Seham M. Al-Mekhlafi; Ahmed Boudaoui; Noura Laksaci; Mohammed H. Alharbi (AIMS Mathematics, 2024)
This paper extends a novel piecewise mathematical model of the COVID-19 epidemic using fractional and variable-order differential equations and fractional stochastic derivatives in three intervals of time. The deterministic models are augmented with hybrid fractional order and variable order operators, while the stochastic differential equations incorporate fractional Brownian motion. To probe the behavior of the proposed models, we introduce two numerical techniques: the nonstandard modified Euler Maruyama method for the fractional stochastic model, and the Caputo proportional constant-Grünwald-Letnikov nonstandard finite difference method for the fractional and variable-order deterministic models. Several numerical experiments corroborate the theoretical assertions and demonstrate the efficacy of the proposed approaches.